The Comparison of Effectiveness of Various Potential Predictors of Response to Treatment With SSRIs in Patients With Depressive Disorder - Bares, Martin; Novak, Tomas; Brunovsky, Martin; Kopecek, Miloslav; Höschl, Cyril (The Journal of nervous and mental disease, 2017)
The substantial non-response rate in depressive patients indicates a continuing need to identify predictors of treatment outcome. The aim of this 6-week, open-label study was (1) to compare the efficacy of a priori defined predictors: ≥20% reduction in MADRS score at week 1, ≥20% reduction in MADRS score at week 2 (RM ≥ 20% W2), decrease of cordance (RC), and increase of serum and plasma level of brain-derived neurotrophic factor at week 1; and (2) to assess whether their combination yields higher efficacy in the prediction of response to selective serotonin re-uptake inhibitors (SSRIs) than when used singly. Twenty-one patients (55%) achieved a response to SSRIs. The RM ≥20% W2 (areas under curve-AUC = 0.83) showed better predictive efficacy compared to all other predictors with the exception of RC. The identified combined model (RM ≥ 20% W2 + RC), which predicted response with an 84% accuracy (AUC = 0.92), may be a useful tool in the prediction of response to SSRIs.
Keywords: Predictive Value of Tests; psychiatrické posuzovací škály; Female; lidé středního věku; Psychiatric Status Rating Scales; Prefrontal Cortex; Electroencephalography; mužské pohlaví; prediktivní hodnota testů; prefrontální mozková kůra; Outcome Assessment, Health Care; deprese nereagující na léčbu; Humans; dospělí; elektroencefalografie; mozkový neurotrofický faktor; Selective Serotonin Reuptake Inhibitors; Prognosis; lidé; Middle Aged; depresivní porucha unipolární; theta rytmus EEG; prognóza; hodnocení výsledků zdravotní péče; ženské pohlaví; Brain-Derived Neurotrophic Factor; Depressive Disorder, Major; Theta Rhythm; Adult; selektivní inhibitory zpětného vychytávání serotoninu; Depressive Disorder, Treatment-Resistant; Male